Logika Keilmuan Kalam: Tinjauan Filsafat Ilmu - Imam Iqbal (UIN Sunan Kalijaga Yogyakarta, 2015)
Some contemporary scholars consider that the logical science of Kalam was patterned apologetic, and dogmatic. This kind of scientific logic makes the Science of Kalam less responsive to developments and changing times. This paper therefore intended to assist the reader in understanding to the assessment. it can be traced through a review of philosophy of science, especially the distinction context of discovery and the context of justification a science. At Science of Kalam, the context of the invention relates to the formulation of science of Kalam based on al-Qur’an and as-Sunnah and residues historicity attached to it. This context shows this pattern of subjective knowledge that actually assessed objectively by the Muslim majority. While the context of justification Kalam can be observed in denial and rejection of the belief that different Mutakallimun using dialectic (al-manhaj al-jadalî; jadaliyyah)and strengthened by evidence demonstrative rational method (al-manhaj al- bahtsî;bahtsiyyah). There are two forms of demonstrative methods commonly used by Mutakallimun, namely analogy and syllogism. The linkage of two kinds of basically a form of scientific logic of Kalam with a pattern on top.[Beberapa sarjana kontemporer menilai bahwa logika keilmuan Kalam itu bercorak apologetik, dan dogmatik. Logika keilmuan semacam ini menjadikan Ilmu Kalam kurang responsif terhadap perkembangan dan perubahan zaman. Tulisan ini bermaksud membantu pembaca dalam memahami penilaian tersebut. Logika keilmuan dapat ditelusuri melalui tinjauan filsafat ilmu, terutama dari distingsi konteks penemuan (the context of discovery) dan konteks justifikasi (the context of justification) sebuah ilmu. Pada Ilmu Kalam, konteks penemuan ilmu ini berkenaan dengan perumusan kalâm berdasarkan al-Quran dan as- Sunnah serta residu-residu historisitas yang melekat padanya. Konteks ini menunjukkan corak subyektif ilmu ini yang justru dinilai obyektif oleh mayoritas Muslim. Sementara konteks justifikasi kalâm dapat dicermati dalam penyangkalan dan penolakan mutakallimûn terhadap kepercayaan yang berbeda dengan menggunakan metode dialektika (al-manhaj al-jadalî; jadaliyyah) dan diperkuat dengan pembuktian rasional yang menggunakan metode demonstratif (al-manhaj al-bahtsî; bahtsiyyah). Ada dua bentuk metode demonstratif yang biasa digunakan oleh mutakallimûn, yaitu qiyâs (analogi) dan silogisme. Keterkaitan dua macam konteks itulah yang pada dasarnya membentuk logika keilmuan Kalam dengan corak di atas.]